Peran Pemangku Kepentingan dalam Pendidikan Lingkungan dalam Pengembangan Program Adiwiyata: Analisis SWOT dan Tingkat Keterlibatan - Siti Badriyah Rushayati; Rachmad Hermawan; Lin Nuriah Ginoga; Siva Devi Azahra (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to analyze the roles of stakeholders in supporting the development of the Adiwiyata School program at Madrasah Ibtidaiyah Muhammadiyah 1 Program Khusus Sukoharjo, which has achieved a national Adiwiyata School award. The methods used include interviews and questionnaires involving school principals, teachers, students, the school committee, the Sukoharjo Regency Environmental Agency, and the Muhammadiyah Elementary and Secondary Education Council. The analysis utilized the Likert Scale to assess stakeholder involvement levels and SWOT analysis (Strengths-Weaknesses-Opportunities-Threats) to formulate development strategies. The results showed that the school principal plays a central role in all aspects, including policies, curriculum, programs/activities, as well as facilities and infrastructure. On the other hand, the Muhammadiyah Elementary and Secondary Education Council contributed the least, limited to policy aspects. Program development is recommended through increasing funding via partnerships, enhancing teacher capacity, and motivating students to implement environmentally conscious and sustainable practices in schools. Keywords: Adiwiyata, Stakeholders, Environmental Education